Selective Maternal Seeding and Rearing Environment From Birth to Weaning Shape the Developing Piglet Gut Microbiome - Chen, Wei; Ma, Jingyun; Jiang, Yiming; Deng, Li; Lv, Ning; Gao, Jinming; Cheng, Jian; Liang, Juan Boo; Wang, Yan; Lan, Tian; Liao, Xindi; Mi, Jiandui (Frontiers in Microbiology, 2022)
The acquisition and development of the mammalian microbiome early in life are critical to establish a healthy host-microbiome symbiosis. Despite recent advances in understanding microbial sources in infants, the relative contribution of various microbial sources to the colonization of the gut microbiota in pigs remains unclear. Here, we longitudinally sampled the microbiota of 20 sow-piglet pairs (three piglets per sow) reared under identical conditions from multiple body sites and the surrounding weaning environment from birth to 28 days postpartum (1,119 samples in total). Source-tracking analysis revealed that the contribution of various microbial sources to the piglet gut microbiome gradually changed over time. The neonatal microbiota was initially sparsely populated, and the predominant contribution was from the maternal vaginal microbiota that increased gradually from 69.0% at day 0 to 89.3% at day 3 and dropped to 0.28% at day 28. As the piglets aged, the major microbial community patterns were most strongly associated with the sow feces and slatted floor, with contributions increasing from 0.52 and 9.6% at day 0 to 62.1 and 33.8% at day 28, respectively. The intestinal microbial diversity, composition, and function significantly changed as the piglets aged, and 30 age-discriminatory bacterial taxa were identified with distinctive time-dependent shifts in their relative abundance, which likely reflected the effect of the maternal and environmental microbial sources on the selection and adaptation of the piglet gut microbiota. Overall, these data demonstrate that the vaginal microbiota is the primary source of the gut microbiota in piglets within 3 days after birth and are gradually replaced by the sow fecal and slatted floor microbiota over time. These findings may offer novel strategies to promote the establishment of exogenous symbiotic microbes to improve piglet gut health.